Automation, COVID-19, and labor markets - Georgios Petropoulos (Asian Development Bank Institute (ADBI), 2021)
Rapid technological progress poses challenges for labor markets. Automation can both displace and create jobs. Currently, an unprecedented digitalization of our economy is underway. Artificial intelligence has become a reality and machines are able to learn how to outperform humans in some cognitive tasks. This ongoing technological transformation of work can interact with the COVID-19 pandemic shock resulting in fewer jobs for the less educated and low-skill workers as well as further decline in the labor share of national income. This paper reviews the impact of automation and artificial intelligence on work and discusses the long-run effects of the pandemic crisis on the workforce. It also presents some thoughts on how the challenges ahead should be addressed through a multidimensional policy response.
Keywords: J11; J21; J23; J24; J31; J38; 330; automation; artificial intelligence; future of work; COVID-19; labor markets